SCIENCE LEARNING DISCOURSE BASED ON CLASSROOM REPRESENTATION PRACTICE TO PROCESS CONCEPT OF MATERIAL PRESSURE - Jihannita Jihannita; Faninda Novika Pertiwi (INSECTA: Integrative Science Education and Teaching Activity Journal, 2022)
Science learning should involve the use of active representation as a medium of communication between teachers and students. This is because representation becomes a medium of communication in the processing of science concepts provided by teachers, and the abilities produced by students themselves during science learning. This study aims to explain class discourse in science learning at SMPN 1 Jetis, based on the focus of discussing the relationship between knowledge representation, and communication patterns. The instruments in this study are questionnaires, and representation ability tests. The data obtained is tabulated in Microsoft Excel, then it is analyzed descriptively. The results showed that science learning at SMPN 1 Jetis was mediated with three types of existing representations, namely active, iconic, and symbolic alternately and simultaneously. The representation ability of students of SMPN 1 Jetis during the learning of the concept of material pressure, reached a score of 81.25 in the category of excellent representation ability; and 2) the shift of the three patterns of combination of representations that exist in science learning at SMPN 1 Jetis directs learning to dialogical, and authoritative communication patterns.